Inhibition of RelA‐Ser536 phosphorylation by a competing peptide reduces mouse liver fibrosis without blocking the innate immune response12. Issue 2 (8th January 2013) - Moles, Anna; Sanchez, Ana M.; Banks, Paul S.; Murphy, Lindsay B.; Luli, Saimir; Borthwick, Lee; Fisher, Andrew; O'Reilly, Steven; van Laar, Jacob M.; White, Steven A.; Perkins, Neil D.; Burt, Alastair D.; et al.
Abstract Phosphorylation of the RelA subunit at serine 536 (RelA‐P‐Ser536) is important for hepatic myofibroblast survival and is mechanistically implicated in liver fibrosis. Here, we show that a cell‐permeable competing peptide (P6) functions as a specific targeted inhibitor of RelA‐P‐Ser536 in vivo and exerts an antifibrogenic effect in two progressive liver disease models, but does not impair hepatic inflammation or innate immune responses after lipopolysaccharide challenge. Using kinase assays and western blotting, we confirm that P6 is a substrate for the inhibitory kappa B kinases (IKKs), IKKα and IKKβ, and, in human hepatic myofibroblasts, P6 prevents RelA‐P‐Ser536, but does not affect IKK activation of IκBα. We demonstrate that RelA‐P‐Ser536 is a feature of human lung and skin fibroblasts, but not lung epithelial cells, in vitro and is present in sclerotic skin and diseased lungs of patients suffering from idiopathic pulmonary fibrosis. Conclusion: RelA‐P‐Ser536 may be a core fibrogenic regulator of fibroblast phenotype. (HEPATOLOGY 2013)